A comparison of student teacher learning from practice in university-affiliated schools in Helsinki and Johannesburg. Issue 1 (1st January 2019) - Lavonen, Jari; Henning, Elizabeth; Petersen, Nadine; Loukomies, Anni; Myllyviita, Ari
ABSTRACT: In a comparative study of student teachers in Finland and South Africa, the researchers aimed to capture students' views of how and what they had learned from practice in two university-affiliated primary schools. With data from survey questionnaires, we found that students in the two customized programmes accentuated different domains of teacher knowledge. The newly established teaching practice school in Johannesburg afforded closer integration of university and school practicum experiences for students than the well-established school in Helsinki. The authors conclude that an innovative teacher education model can be re-invented in a significantly different context and also add new dimensions to the original.